Dental health problems and treatment-seeking behavior among special need school students in Amhara region, Ethiopia - Amare Teshome Tefera; Biruk Girma; Aynishet Adane; Abebe Muche; Tadesse Awoke Ayele; Kefyalew Ayalew Getahun; Zelallem Aniley; Semira Ali; Simegnew Handebo (BMC, 2021)
Abstract Background Oral diseases are a public health concern with a significant impact on the quality of life of individuals. Children with special needs face significant challenges in carrying out oral hygiene due to their disability, and they are more prone to poor oral health and illnesses. This study assessed dental health problems and treatment-seeking behaviors of special needs school students in Amhara region, Ethiopia. Methods An institution-based cross-sectional study was conducted from November 2020 to April 2021, in eight special needs schools located in the Amhara Regional State, Ethiopia. A total of 443 randomly selected special needs students were included. Data were collected using a structured interview-administered questionnaire. Bivariable and multivariable logistic regression models were fitted to identify factors associated with oral health problems and treatment-seeking behavior. A p-value of less than 0.05 was used to declare statistical significance. Results The prevalence of self-reported dental health problems and treatment-seeking behaviors among special needs school students was 46.1% (95% CI: 41.4%, 50.7%) and 60.3% (95% CI: 53.4%, 66.8%), respectively. Place of residence, grade level, religious affiliation, years lived with disability, and knowledge of dental health-related risk behaviors were associated with dental health problems. Whereas, place of residence, being hearing impaired, and having prior information about dental health problems were associated with dental treatment-seeking behavior. Conclusions A significant number of special needs students reported dental problems and about 40% of them did not seek dental treatment. Oral hygiene practice and access to dental care services are important in the prevention of dental problems. Hence, oral hygiene promotion programs focusing on oral hygiene practice and dental treatment services are needed in special needs schools. It is also strongly suggested to incorporate oral health related information in health-related academic lessons to enhance optimum oral health among special needs students.